Global seroprevalence of Toxoplasma gondii in pregnant women: a systematic review and meta-analysis - Salari, Nader; Rahimi, Avijeh; Zarei, Hosna; Abdolmaleki, Amir; Rasoulpoor, Shabnam; Shohaimi, Shamarina; Mohammadi, Masoud (BioMed Central, 2025)
Background: Toxoplasmosis in pregnancy is associated with serious and irreversible maternal and fetal detrimental consequences. Also, different seroprevalence of Toxoplasma gondii in pregnancy is reported in many countries. The present systematic review and meta-analysis study aimed to determine the global seroprevalence of Toxoplasma gondii in pregnant women. Methods: This study was conducted based on the PRISMA 2020 criteria. Initial searching was conducted using MeSH (Medical Subject Headings)-based keywords with no time limitation (by August 1, 2024). Collected papers were transferred to Citation Management Software (EndNote). Duplicate studies were merged and primary and secondary screenings were applied based on the inclusion/exclusion criteria. Validation was considered to find high-quality assessments. Finally, eligible extractable papers were enrolled for data collection. Data was analyzed using Comprehensive Meta-Analysis software (v.2) The random effects model was used in case of I2 index above 50%.In order to investigate the factors affecting the heterogeneity of studies, meta-regression tests were used to examine factors such as sample size and year of study. Results: One hundred thirty-eight eligible studies with a total sample size of 135,098 pregnant women individuals were selected for data extraction and analysis. The heterogeneity index was found high (I2:98.9) and the random effect model was used for analysis. The egger test revealed the absence of publication bias in collected studies (p:0.088). Thus, the global seroprevalence of Toxoplasma gondii in pregnant women was reported at 36.6% (95%CI:33.7–39.6). the highest prevalence reported based on meta-analysis was reported in South America with 52.8% (95% CI:46.6–59), while only 15 studies were reviewed in this continent, most of which were in Brazil. Therefore, after the continent, the highest prevalence reported was reported in Africa with 46.8% (95% CI:39.5–54.3). Also, the lowest prevalence reported based on meta-analysis was in North America with 19.7% (95% CI:8.4–39.6) and Europe with 24.6% (95% CI:17.8–32.9). Conclusion: This study revealed a high level of seroprevalence of Toxoplasma gondii in pregnant women worldwide. This value mostly depends on the individual's age, lifestyle, and disease awareness regarding toxoplasmosis in pregnant women. Thus, public awareness, along with comprehensive health programs regarding the detrimental effects of toxoplasmosis in pregnant women, seems necessary for prevention or even early diagnosis of toxoplasmosis in pregnant women.